PENGARUH METODE LATIHAN SMALL-SIDED GAMES TERHADAP KETEPATAN UMPAN (PASSING) PADA PEMAIN SSB GERHANA JALAKSANA KABUPATEN KUNINGAN - Muhammad Ade Haerudin (STKIP Muhammadiyah Kuningan, 2022)
The background of this research problem is that there are still many students who are not precise in passing in a soccer game, the students' passing has not been directed to the specified target. This study aims to determine the effect of the small sided games training method on the accuracy of passing on SSB GERHANA players. The subjects of this study were students who took part in SSB GERHANA. The population in this study were all soccer players of the SSB GERHANA club. The sampling technique used is total sampling, which amounts to 20 people. This study was conducted with the aim of knowing how much influence the practice of small-sided games has on the accuracy of the bait on SSB GERHANA players. The research method that the author uses to test the truth of the hypothesis that has been proposed is the experimental method. This method is in accordance with the nature of the problem to be studied by the author, namely the effect of small-sided games training on the accuracy of passing on soccer players SSB Eclipse. Based on the results of research that has been obtained by analyzing data and testing hypotheses, it can be concluded that